Hubungan Antara Waktu Tunggu dan Respon Kepuasan Konsumen Terhadap Pelayanan di Instalasi Farmasi Puskesmas Teras dan Puskesmas Sawit Boyolali - Annita Fitri Fauziah; Hanugrah Ardya C. S; Joko Santoso (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Satisfaction is the response from customers or service users to what they receive. Based on the Community Satisfaction Index conducted by the Boyolali District Health Office in 2023, a high score of 82.54% was obtained. However, in several studies related to satisfaction, some dimensions still fall below the level of alignment between expectations and reality, particularly regarding service timeliness, providing opportunities for patients to ask questions, and creating a safe environment. Waiting time is the period from when a patient submits a prescription until they receive their medication. This study aims to determine the relationship between waiting time and consumer satisfaction response to services at the pharmacy installations of Sawit and Teras Community Health Centers in Boyolali in 2023. The method used was analytic with a cohort design, data collection employed purposive sampling, and the research was analyzed using a Chi-square test with an obtained P-value of 0.000 (<0.05). The research findings indicated that 95% of service waiting times met the standards, while 5% did not. This study concluded that there was a relationship between waiting time and patient satisfaction response to services at the pharmacy installations of Teras and Sawit Community Health Centers in Boyolali.